Counterfactual Thinking and Entrepreneurial Self‐Efficacy: The Moderating Role of Self‐Esteem and Dispositional Affect. (3rd July 2011) - Arora, Punit; Haynie, J. Michael; Laurence, Gregory A.
<x xml:space="preserve">Abstract</x> Scholars have suggested that counterfactual thinking may play an important role in entrepreneurship; however, empirical research positioned to inform the nature of this relationship has been equivocal. In this study, we draw on the tenets of social cognition theory as a basis to investigate the relationship between counterfactual thinking and the dispositional attributes of the entrepreneur, hypothesizing concomitant influences upon the entrepreneur's self‐efficacy. Based on a survey of 138 entrepreneurs, our findings suggest that the implications of counterfactual thinking for entrepreneurial self‐efficacy are moderated by individual differences based in the dispositional attributes of the entrepreneur.